Gait speed and pedestrian crossings in COPD. Issue 2 (5th May 2017) - Nolan, Claire M; Kon, Samantha S C; Patel, Suhani; Jones, Sarah E; Barker, Ruth E; Polkey, Michael I; Maddocks, Matthew; Man, William D-C
Abstract : The assumed minimum walking speed at pedestrian crossings is 1.2 m/s. In this prospective cohort study, usual walking speed was measured over a 4 m course in 926 community-dwelling, ambulatory patients with stable COPD. Mean (SD) walking speed was 0.91 (0.24) m/s with only 10.7% walking at a speed equal or greater than 1.2 m/s. In order for 95% of this cohort to safely negotiate a pedestrian cross, traffic lights would have to assume a minimum walking speed of 0.50 m/s (2.4 times longer than current times). The current assumed normal walking speed for pedestrian crossings is inappropriate for patients with COPD. The studies were registered on clinicaltrials.gov and these data relate to the pre-results stage: NCT01649193, NCT01515709 and NCT01507415 .